LEGAL REVIEW OF UNLAWFUL ACTS IN LAND DISPUTES - Sadat, Anwar; Prasetyotomo, Heru; L., Pakerti Luhur; Nazara, Zelima; Kusuma, Nurul Widya; Irawan, Teguh (JILPR Journal Indonesia Law and Policy Review, 2025)
Law and jurisprudence stipulate that the perpetrator must have schuldelement, or an element of fault, in committing his/her act in order to be covered by Article 1365 concerning Unlawful Acts. Liability under Article 1365 of the Civil Code does not include liability without fault (strict liability). Jurisprudence recognizes the concept of immaterial losses, which will be assessed in monetary form, in contrast to losses arising from breach of contract, which only discusses material losses, and losses arising from unlawful acts. Decision of the Sukoharjo District Court Number 32/Pdt.G/2007/Pn.Skh. The case began when the plaintiff sold a building and a plot of land to the defendant. After both parties agreed on the price of the land, the defendant paid the plaintiff in cash and the remainder by check, but the check turned out to be empty when the plaintiff cashed it at Bank BCA. The formulation is 1) What is the perspective of Unlawful Acts in Civil Law? 2) How to resolve land and building sale and purchase disputes through lawsuits for unlawful acts at the Sukoharjo District Court? and 3) What are the legal consequences of the judge's decision regarding land and building sale and purchase disputes at the Sukoharjo District Court? The method used is the normative legal research method, which is to examine relevant laws and regulations or apply them to a particular legal problem. Law enforcers are advised to apply these elements carefully in order to achieve justice in each case. Victims also need to be given support in proving the existence of losses and causal relationships with the actions of the perpetrators. In addition, it is important to conduct socialization to the community regarding the definition of unlawful acts, the rights of victims, and the legal obligations of perpetrators to increase legal awareness in community life.